Saint Omer [videorecording (DVD)] - Diop, Alice, 1979-; David, Amrita; NDiaye, Marie; Kagame, Kayije; Malanda, Guslagie; Dréville, Valérie; Petit, Aurélia (Criterion collection, 2024)
Bringing a documentarian's sense of open-ended inquiry to her first narrative feature, writer-director Alice Diop constructs a morally and emotionally layered courtroom drama unlike any other. When she travels to Saint-Omer, France, to attend the trial of a young Senegalese woman accused of murdering her infant daughter, novelist Rama finds herself shaken to the core by a case that proves to have profound resonances with her own life. Interweaving complex themes of mother-daughter bonds, immigrant alienation, and postcolonial trauma into a piercing portrait of two mysteriously connected women, Diop forgoes mere questions of guilt and innocence to plumb the unsettling unknowability of the human soul.